Acceptability of the Direct Health Facility Financing (DHFF) initiative in Tanzania: A mixed methods process evaluation of the moderating factors. (24th December 2021) - Kalolo, Albino; Kapologwe, Ntuli A.; Samky, Hendry; Kibusi, Stephen M.
Abstract: Despite wide agreement that stakeholder acceptability plays a critical role in an intervention's effectiveness, gaps remain on understanding acceptability of complex health financing interventions. We aimed to understand the moderators of acceptability of the Direct Health Facility Financing (DHFF) initiative across primary health facilities in Tanzania. Employing a mixed methods approach and guided by the theoretical framework for acceptability (TFA), we collected data from implementers and their supervisors using a structured questionnaire and semi‐structured interview guides. We analysed data using a chi square test, logistic regression, and thematic analysis. We recruited 238 participants, of whom 71% were females and 54% were below 37 years old. Acceptability was found to be 63% and received high rating in qualitative interviews. Moderators of acceptability included sex (AOR = 1.93, p = 006), work experience (AOR = 3.47, p = 0.001), knowledge (13.8, p = 0.00), supportive work environment (AOR = 2.28, p = 0.019), and capability to implement the programme (AOR = 0.12, p = 0.00). Moderators reported in qualitative interviews related to individual and contextual factors. This study suggests that the DHFF initiative is acceptable and influenced by factors operating at the individual level and beyond. Addressing moderators of acceptability as programs are designed and implemented is the holy grail of acceptability of complex interventions. Highlights: Effectiveness of any intervention depends on its level of acceptability by stakeholders. This study demonstrates that the Direct Health Facility Financing (DHFF) initiative was highly accepted amid the influence of individual, contextual, and program factors. The Theoretical framework for acceptability (TFA) provided a clear view of acceptability of the initiative and the likelihood of its utilization in routine appraisal of acceptability of complex interventions. Designers and supervisors of complex programs, should consider drivers of acceptability and design implementation guidance and strategies accordingly.